2017
DOI: 10.1371/journal.pone.0166806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climatic Factors and Population Density on the Distribution of Dengue in Sri Lanka: A GIS Based Evaluation for Prediction of Outbreaks

Abstract: Dengue is one of the major hurdles to the public health in Sri Lanka, causing high morbidity and mortality. The present study focuses on the use of geographical information systems (GIS) to map and evaluate the spatial and temporal distribution of dengue in Sri Lanka from 2009 to 2014 and to elucidate the association of climatic factors with dengue incidence. Epidemiological, population and meteorological data were collected from the Epidemiology Unit, Department of Census and Statistics and the Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 24 publications
7
63
1
Order By: Relevance
“…Population density is well known to have a contribution on dengue transmission, previous research in Sri Lanka found that dengue incidence associated with population density where high dengue incidence has occurred in high population density. 10 In this research, we found a similar result; it seems that the number of dengue incidence has an association with population density. Areas in the urban characteristic such as Depok sub-district then next Mlati, Godean and Gamping are majority have higher cases compared to low population subdistrict which is located in rural or transition rural-urban.…”
Section: Discussionsupporting
confidence: 77%
“…Population density is well known to have a contribution on dengue transmission, previous research in Sri Lanka found that dengue incidence associated with population density where high dengue incidence has occurred in high population density. 10 In this research, we found a similar result; it seems that the number of dengue incidence has an association with population density. Areas in the urban characteristic such as Depok sub-district then next Mlati, Godean and Gamping are majority have higher cases compared to low population subdistrict which is located in rural or transition rural-urban.…”
Section: Discussionsupporting
confidence: 77%
“…An analysis of extensive data on dengue cases reported by the Epidemiology Unit of the Ministry of Health, indicates that the pattern of development of an outbreak follows the trend of the equation (15) to a significant level of confidence [18]. The distribution of dengue cases in Sri Lanka from 2010 to 2017 are plotted in Figure1a.…”
Section: Original Articlementioning
confidence: 93%
“…However, mosquitoes which bite at night may also act as dengue vectors. Increased human population density, effect of climate on mosquito breeding and presence of several stereotypes of the virus and human reservoirs with marginal to severe clinical manifestations Ceylon Medical Journal 2018; 63: 58-64 DOI: http://doi.org/10.4038/cmj.v63i2.8670 complicate the epidemiology of the disease [18][19][20]. The simple model presented here examines the development of dengue infection in an environment of constant human and mosquito populations.…”
Section: The Mathematical Modelmentioning
confidence: 99%
“…heat cramps, heat syncope, heat exhaustion, heat stroke and possible death [25][26][27]. These studies all identified temperature extremes as a factor that can affect physiological functioning, mood behavior and workplace productivity, especially amongst outdoor workers.…”
Section: Research Gapsmentioning
confidence: 99%